Formation of step density shock waves on vicinal NaCl(100) growth surfaces - Kulyk, O.P.; Podshyvalova, O.V.; Andrieieva, O.L.; Tkachenko, V.I.; Gnatyuk, V.A.; Aoki, T. (Вопросы атомной науки и техники, 2022)
The morphology of the growth surface near NaCl(100), formed during the pore motion in a crystal due to the temperature gradient, has been studied by the electron microscopic method of vacuum decoration. It is shown that at T = 950 K and Δμ/kΤ = 4·10⁻³, the profile of the vicinal surface in the <11> direction is represented by monoatomic steps, while in the <10> direction, as the surface curvature increases, there is a grouping of steps with the formation of macrosteps – bunches of elementary steps separated by areas of atomically smooth terraces. The sawtooth dependence of the step density on the longitudinal coordinate is described by a particular solution of the Burgers equation for a shock wave. Data on the parameters of three shock waves and the time of their formation are obtained.